PENERAPAN METODE DISKUSI UNTUK MENINGKATKAN KOGNITIF SISWA KELAS VII SMPN 7 KUNTODARUSALAM: The Application of the Discussion Method to Improve Cognitives of Class VII Students of SMPN 7 Kuntodarusalam - Suryanti Suryanti (UIR Press, 2019)
This study aims to determine the application of discussion methods to improve cognitive grade VII students SPMN 7 Kuntodalamalam, Research data retrieval carried out from January to February 2017 in Class VII 7 Kuntodarussalam Middle School Academic Year 2017/2018. The research subjects were 32 students consisting of 10 female students and 22 male students. Data collection includes: the value of discussion, Quiz, PR and Block Exams. Using descriptive analysis. The results obtained from 6 indicators in the discussion process in cycle I and sikulus II were highest in indicator 1 (attention to discussion material) with an average of 97.97% in very good category. in the first cycle of indicator 5 (Respecting the suggestions and opinions of fellow discussion participants) with an average of 61.09% (category is very lacking), in the second cycle the lowest was on indicator 6 (Concluding material) with an average of 64.13% ( category is very lacking). The average value of the discussion of meeting students from the first cycle and the second cycle the lowest value at the first meeting with a value of 76.35 (lack of category) and a value of 82.06 (sufficient category), the highest in the second cycle of meeting 2 with a value of 79.53 (sufficient category), while in the second cycle the highest at meeting III with a value of 82.06 (sufficient category). the average quiz score in the first cycle and the second cycle the lowest Quiz 3 with a value of 80.8 (sufficient category), the highest on quiz 6 with a value of 84.4 (good category). the value of homework assignments for students is the lowest in the first cycle with a value of 88.7 and the second cycle the value of 91.3 is very good. Nilau UB obtained from the first cycle is the lowest with the highest value of 81.9 and Cycle II with a value of 84.2 with a good category. It can be concluded that the application of the discussion method can improve the cognitive grade VII of Kuntodarusalam 7th Middle School.Keywords: metode diskusi,kognitif